Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2022
DOI: 10.1155/2022/7827980
|View full text |Cite|
|
Sign up to set email alerts
|

Influence of Aerobic Exercise Load Intensity on Children’s Mental Health

Abstract: As people have become more aware in recent years, aerobic physical exercise plays an important role in alleviating people’s mental health problems. However, traditionally, it is believed that young children do not have mental health problems. To help people change this fixed idea, and to study how to correctly adjust the load intensity of aerobic physical exercise under the condition of limited physical fitness of young children, and accurately help children’s mental health development, this paper studies the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 19 publications
(15 reference statements)
0
3
0
Order By: Relevance
“…Consequently the World Health Organization recommends that children and adolescents participate in at least 60 minutes of physical activity per day to achieve optimal health and development outcomes [6]. Further, when individuals participate in more physical activity and/or physical activity performed at higher intensities, they experience more potent and additional health benefits [7][8][9][10]. However, current data demonstrates that approximately 80% of children and adolescents globally [11] and across Australia [12] are considered insufficiently active.…”
Section: Introductionmentioning
confidence: 99%
“…Consequently the World Health Organization recommends that children and adolescents participate in at least 60 minutes of physical activity per day to achieve optimal health and development outcomes [6]. Further, when individuals participate in more physical activity and/or physical activity performed at higher intensities, they experience more potent and additional health benefits [7][8][9][10]. However, current data demonstrates that approximately 80% of children and adolescents globally [11] and across Australia [12] are considered insufficiently active.…”
Section: Introductionmentioning
confidence: 99%
“…Tis article has been retracted by Hindawi following an investigation undertaken by the publisher [1]. Tis investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process:…”
mentioning
confidence: 99%
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [ 1 ]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process: Discrepancies in scope Discrepancies in the description of the research reported Discrepancies between the availability of data and the research described Inappropriate citations Incoherent, meaningless and/or irrelevant content included in the article Peer-review manipulation …”
mentioning
confidence: 99%